Utilization of Corn Waste As a Feed On Farmer Group Satwa Winangun - D. M. R., Cahyanti; Ardika, I N.; Astawa, I P. A. (Jurnal Peternakan Tropika; Vol 7 No 3 (2019): Issue 7 No. 3 - 2019; September - December 2019, 2019)
This study was carried out with the aim of utilizing available corn waste as feed given to cattle during the dry season in the Winangun Animal Livestock Farmers Group. The method used in Student Work Practices (PKM) to obtain data is the observation method and the method of direct interviews, the observation method is carried out by direct observation of existing conditions while the interview method is carried out question and answer directly to the group leader and the breeders in the cowshed .Based on observations made on the KTT Satwa Winangun, it can be concluded that the feeding of corn plant waste, namely corn cobs, corn stalks, corn leaves, can meet the needs of cattle with the difference in feeding, amounting to BK 4.9 kg, TDN 1.99 kg, Protein -6.11%, Fat 7.8%, Ca 26.32%, P 6.55% higher than the needs of cattle so they can reproduce well. Corn waste feed can be a substitute feed for dry rice straw in the dry season for livestock because the rice straw content is almost the same as the corn waste content. Keywords : Corn waste, cows, nutrition needs